2019
DOI: 10.1016/j.fertnstert.2018.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ischemic placental disease in fresh and frozen embryo transfer cycles

Abstract: Objectives: To evaluate the association of fresh and frozen embryo transfer with the development of ischemic placental disease (IPD), hypothesizing that differences in implantation environment affect placentation and thus pregnancy outcomes. Design: We performed a secondary analysis of a retrospective cohort study of deliveries linked to IVF cycles. Setting: Tertiary hospital and infertility treatment center. Patient(s): We included all women who underwent an autologous IVF cycle and had a live-born infant or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
0
32
1
Order By: Relevance
“…Previous studies have shown a lower risk of SGA and low birth weight in pregnancy conceived following FET as compared to fresh embryo transfer 6,41,42,51 . However, all these studies are limited by a high risk of selection bias, since the characteristics of the women undergoing fresh embryo transfer are different from those undergoing FET.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a lower risk of SGA and low birth weight in pregnancy conceived following FET as compared to fresh embryo transfer 6,41,42,51 . However, all these studies are limited by a high risk of selection bias, since the characteristics of the women undergoing fresh embryo transfer are different from those undergoing FET.…”
Section: Discussionmentioning
confidence: 99%
“… Feng 2012 [ 25 ] Women with various infertile causes 31.02 ± 3.69/ 31.60 ± 3.56 604/ 384 Retrospective study Jan 2009 to Dec 2010 IR, CPR, MR, LBR, MPR, EPR, PTD, LBW, Stil, NM Ferraretti 1999 [ 26 ] Patients at risk of OHSS 31.46 ± 2.4/ 31.66 ± 2.8 67/58 Prospective RCT Jan 1996 to Jul 1997 CPR, LBR, PR Ginström 2019 [ 27 ] Singletons born after in Sweden 34.9 ± 5.2 /34.1 ± 4.3 9726/24,365 Retrospective cohort study 2005 to 2015 GDM, PP, PA, PPH, PIH, Healy 2010 [ 28 ] Women with singleton births in Victoria Australia No statement 4058/2045 Retrospective cohort study 1991 to 2004 PP, PA, PH Henningsen 2011 [ 29 ] Singleton born after fresh ET or FET No statement 716/716 Retrospective cohort study 1994 to 2008 LBW Henman 2005 [ 30 ] Patients with three or more usable blastocysts < 38 years 121/156 Prospective study Apr 2000 to Dec 2001 IR, CPR, LBR, MPR Hwang 2019 [ 31 ] Singleton infants born to Massachusetts women who conceived by fresh or FET No statement 12,390/ 2101 Retrospective cohort study. July 2004, to Dec 2013 Preterm, LGA, SGA, LBW, Birth defects Ishihara 2014 [ 32 ] Women undergoing SET Any age 33,559/118866 (5981/27408 singletons) Retrospective study 2008 to 2010 CPR, MR, MPR, EPR, PP, PA, PIH, LGA, SGA, LBW, HBW, Stil Johnson 2019 [ 33 ] Women who underwent an autologous IVF cycle 35.8 (32.8–38.8)/36.3 (33.0–39.8) …”
Section: Resultsmentioning
confidence: 99%
“…These findings thus differ from our results. Moreover, a recent publication also reported that the risk of preeclampsia was lower when there was a high peak E2 level [33].…”
Section: Discussionmentioning
confidence: 95%